EFEKTIFITAS PROGRAM DIDIKAN SUBUH DALAM PENDIDIKAN KARAKTER ANAK-ANAK DESA AIR PUTIH - Hidayani, Siti; Listiani, Elsita; Mellisa, Selvia (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
This study raised the effectiveness of the dawn education program in the character eduction of the children of Air Putih village, how the characters were acquired by these students. The method used in this research is descriptive qualitative with the target students of the dawn education program. To collect data the authors used observation, interview, and documentation methods as data collection tools, and data analysis techniquesused data reducation, data display and verification, and data validity by comparing the results of observations with interviews. Based on the results of the research, it can be concluded that in its implementation it can be said that it has been carried out well, even thought it has a few obstacles. As for some of the characters that the children of Air Putih village can get in this dawn education program include components: time discipline, developing worship habits, educating values and the spirit of worship, making children love mosques and being able to grow children"™s mentality. The obstacles are: the minimum number of participants, limited and lack of local community support, barriers to technical coordination, and time discipline constraints